ANALISIS STAKEHOLDERS DALAM PENGEMBANGAN PROGRAM DIKLAT DI BALAI DIKLAT APARATUR KEMENTERIAN KELAUTAN DAN PERIKANAN STAKEHOLDERS ANALYSIS IN DEVELOPMENT OF TRAINING PROGRAM ON TRAINING OFFICE OF APPARATUS MINISTRY OF MARINE AFFAIRS AND FISHERIES - Yudistira Adi Nugroho (LPPM Universitas Buana Perjuangan Karawang, 2019)
The results of the identification of training needs indicate that there are still several types of training that cannot be implemented. One of the contributing factors is the development of training programs in both technical training and functional training have not been fully implemented. This study aims to analyze the role and interests of stakeholders in the development of training programs at the Training Office for Apparatus of the Ministry of Marine Affairs and Fisheries. For research purposes, the method used in this study consisted of qualitative descriptive methods. Data retrieval is done by means of field research through interviews with several informants. The selection of informants is based on purposive sampling technique, namely the technique of selecting informants to get data sources based on people who are considered to know the best about what the researchers expect. While data analysis is done by reducing data, presenting data, and deducing data. The results showed: 1) Key stakeholders in the development of the training program consisted of the Marine and Fisheries Counseling and Training Center, Head of the Apparatus Training Center (BDA), Head of Training Organization Section, Head of Program, Monitoring and Evaluation Section, Trainers, and Private Professional, 2) Key stakeholders have a large role and interest in the development of training programs, and 3) Development of training programs needs to involve other stakeholders, namely latent stakeholders, defenders stakeholder, and aphatetic stakeholders.Keywords: Roles, Interest, Stakholder, Training Program Hasil identifikasi kebutuhan diklat menunjukkan bahwa masih terdapat beberapa jenis diklat yang belum dapat dilaksanakan. Salah satu faktor penyebabnya adalah pengembangan program diklat baik diklat teknis maupun diklat fungsional belum dapat dilaksanakan sepenuhnya. Penelitian ini bertujuan untuk menganalisis peran dan kepentingan stakeholder dalam pengembangan program diklat di Balai Diklat Aparatur Kementerian Kelautan dan Perikanan. Untuk keperluan penelitian, metode yang digunakan pada penelitian ini terdiri dari metode deskriptif kualitatif. Pengambilan data dilakukan dengan cara penelitian lapangan melalui wawancara dengan beberapa informan. Pemilihan informan didasarkan pada teknik purposive sampling yaitu teknik pemilihan informan untuk mendapatkan sumber data berdasarkan orang yang dianggap paling mengetahui tentang apa yang diharapkan peneliti. Sedangkan analisis data dilakukan dengan cara mereduksi data, menyajikan data, dan menyimpulkan data. Hasil penelitian menunjukkan : 1) Stakeholder kunci dalam pengembangan program diklat terdiri dari Pusat Pelatihan dan Penyuluhan Kelautan dan Perikanan (Puslatluh KP), Kepala Balai Diklat Aparatur (BDA), Kepala Subbagian Tata Usaha BDA, Kepala Seksi Program, Monitoring, dan Evaluasi BDA, Widyaiswara BDA dan Swasta Profesional, 2) Stakeholder kunci memiliki peran dan kepentingan yang besar dalam pengembangan program diklat, dan 3) Pengembangan program diklat perlu melibatkan stakeholder lain yakni stakholder latent, stakholder defender, dan stakholder aphatetic. Kata Kunci: Peran, Kepentingan, Stakeholder, Program Diklat